The Effect of Digital Leadership Style and Employee Well-Being on Employee Performance with Job Satisfaction as an Intervening Variable at the Food Security and Agriculture Office of Binjai City - Florentina Boangmanalu; Kiki Farida Ferine; Abdi Sugiarto (CV. Doki Course and Training, 2026)
The increasing integration of digital technology in public-sector organizations has emphasized the importance of digital leadership and employee welfare in improving organizational outcomes. This study aims to examine the effects of digital leadership style and employee welfare on employee performance, with job satisfaction serving as an intervening variable, at the Food Security and Agriculture Office of Binjai City. This research employed a quantitative associative design to analyze both direct and indirect relationships among the variables. The research population consisted of all 40 employees of the institution, and a saturated sampling (census) technique was applied, involving all employees as respondents. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS version 3.3.3. The results reveal that digital leadership style has a positive and significant effect on job satisfaction, indicating that leadership practices oriented toward digital adaptation, communication, and technology utilization enhance employees’ satisfaction levels. Employee welfare is also found to have a positive and significant effect on job satisfaction, highlighting the importance of adequate compensation, social security, and work facilities in shaping positive employee attitudes. However, digital leadership style does not have a significant direct effect on employee performance. In contrast, employee welfare shows a strong and significant direct influence on employee performance, demonstrating that welfare fulfillment is a dominant factor in improving productivity and work outcomes. Furthermore, job satisfaction does not have a significant effect on employee performance and does not mediate the relationship between digital leadership style and employee performance, nor between employee welfare and employee performance